PENINGKATAN AKTIVITAS BELAJAR SISWA TEMATIK TERPADU MENGGUNAKAN MODEL BAMBOO DANCING BERBANTUAN MEDIA KARTU DI KELAS IV SDN 05 ALANG RAMBAH - Hendrizal; Utami, Utari (LP2M Universitas Adzkia, 2024)
This study was motivated by the low level of integrated thematic learning activity in Grade IV at SDN 05 Alang Rambah, where students were not actively involved in oral, visual, listening, and mental activities during the learning process. The purpose of this study was to describe the improvement of students’ learning activities through the Bamboo Dancing model assisted by flashcard media. This research employed a classroom action research design using both qualitative and quantitative approaches, conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through observation and documentation, using observation sheets to assess learning activities and photographic documentation. The results showed an improvement in students’ learning activities, with oral activities increasing from 64.05% to 76.56%, visual activities from 65.09% to 78.64%, listening activities from 66.14% to 79.16%, and mental activities from 67.70% to 80.20%. These findings indicate that the application of the Bamboo Dancing model assisted by flashcard media effectively improves students’ learning activities, reaching a good category.